District Policy being ahead of the Urban in Integrated Planning of Metropolitan Municipalities in Turkey, the Example of Konya - Sinan Levend; Rahmi Erdem (European Regional Science Association (ERSA), 2014)
This study aims at analyzing the impacts of administrative problems resulting from the two level form of urban government whose framework is outlined in the Law for Metropolitan Municipalities, over the notion of integrated planning. It is suggested that it would be impossible to mention a sustainable integrated planning notion since the institutions entitled to planning within the metropolitan municipalities are not always in coordination. Within the scope of this study, first the provisions of the Law for Metropolitan Municipalities were reviewed; afterwards the process regarding the chosen sample area was discussed accordingly. The method of this research was based on the elaborate analysis of both the sample area and of the Law on Metropolitan Municipalities. At the end of the study, it was concluded that the problems results from the integrated planning of Konya, the share of planning authorization among the levels, the fact that the metropolitan municipal council consists totally of district municipal council members and the existence of certain discrepancies in the law's content in terms of authorities and responsibilities required for planning metropolitan areas. In the final part of the study, solutions for the identified problems were offered.
Keywords: 330; Urban Government; Urban Politics; Metropolitan Municipality; Konya-Turkey